Strategic performance measurement and managerial performance: the mediating role of job satisfaction and psychological empowerment - Hassan Haslina, Maelah Ruhanita, Mohd Amir Amizawati (Universiti Pendidikan Sultan Idris, 2016)
Strategic performance measurement and managerial performance: the mediating role of job satisfaction and psychological empowerment by Hassan Haslina, Maelah Ruhanita, Mohd Amir Amizawati,